Growth Performance of Soybean (Glycine max L. Merrill) treated with biochar under cadmium Stress: Effect of biochar on soybean (South Asian Journal of Agriculture, 2023)
Cadmium (Cd) is a non-essential heavy metal that adversely affects plant growth. Biochar is predicted to facilitate plant growth. Under cadmium stress condition the effects of biochar on Soybean seedling growth, biomass production and SPAD value were poorly understood. In the current pot study Soybean was grown under different biochar and Cd combinations: 0% biochar and no Cd (control), 1.5% biochar, Cd (100 mg kg-1 of soil), Cd (100 mg kg-1 of soil) + 1.5% biochar. The results exhibited that under Cd stress shoot fresh weight (SFW), root fresh weight (RFW), shoot dry weight (SDW), root dry weight (RDW), shoot length (SL), root length (RL), whole plant biomass, stress tolerance index (%) and SPAD value decreased in Soybean, while root and shoot length ratio increased in comparison to control. Application of biochar solely or in addition of Cd enhanced SFW (14.07% with solely and 126.44% with Cd); RFW, SDW, RDW, SL and RL (156.66%, 55.89%, 61.29%, 21.14% and 16.62% with Cd, respectively), whole plant biomass (8.41% with sole biochar and 137.77% with Cd) and SPAD value (34.94% with Cd) in Cd-stressed Soybean. The sole application of biochar or Cd increased stress tolerance index (%) (SFSTI, RFSTI, SDSTI, RDSTI, SLSTI and RLSTIas recorded 114.04%, 92.25%, 104.47%, 105.78%, 100.73% and 99.22%, respectively; SFSTI, RFSTI, SDSTI, RDSTI, SLSTI and RLSTIvalue by 125.90%, 156.67%, 55.79%, 61.31%, 30.16% and 16.62% with Cd, respectively) in Cd-stressed Soybean. These results demonstrate that soil amendment with 1.5% biocharenhanced growth, biomass production and SPAD value of Soybean under Cd stress. It is therefore recommended that biochar can be used as effective tool to mitigate the detrimental effect of Cd stress on Soybean seedlings.South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 22-30